Interlayer space engineering-induced pseudocapacitive zinc-ion storage in holey graphene oxide-bearing vertically oriented MoS2 nano-wall array cathode for aqueous rechargeable Zn metal batteries - Babu, Athira; Dilwale, Swati; Kurungot, Sreekumar (Small, 2024)
Transition metal dichalcogenides, particularly MoS2, are acknowledged as a promising cathode material for aqueous rechargeable zinc metal batteries (ARZMBs). Nevertheless, its lack of hydrophilicity, poor electrical conductivity, significant restacking, and restricted interlayer spacing translate into inadequate capacity and rate performance. Herein, the unique porous structure and additional functional groups present in holey graphene oxide (hGO) are taken advantage of to dictate the vertical growth pattern of oxygen-doped MoS2 nanowalls (O-MoS2/NW) over the hGO surface. Compared to conventional graphene oxide (GO), the presence of nano-pores in hGO facilitates the homogeneous dispersion of Mo precursors and provides stronger interaction sites, promoting the uniform vertical alignment of O-MoS2/NW. The synergistic interaction between O-MoS2-NW and hGO translates to enhanced electron conductivity, efficient electrolyte penetration, enhanced interlayer spacing, reduced restacking, and enhanced surface area. As a consequence of precise control of various factors that decide the overall battery performance, a high discharge capacity (227 mAh g(-1) at 100 mA g(-1)) cathode material with significantly lower charge transfer resistance (66 Omega) compared to pristine O-MoS2 (153 Omega) is developed. These findings underscore the potential of hGO as a multifunctional platform for nanoengineering high-performance cathode materials for the next generation of efficient and durable ARZMBs.
Keywords: aqueous rechargeable zinc metal battery; holey graphene oxide; hydrophilicity tuning; interlayer space engineering; oxygen-doped MoS2; transition metal dichalcogenide; vertical nanowall